Development of system for selecting suitable landing location inside the local hazard area - Kurdel, Pavol; Pastir, David; Zaremba, Jaroslav; Korba, Lukas; Yakovlieva, Anna (Eastern-European Journal of Enterprise Technologies, 2021)
In the area of successful landing and guidance of the aircraft on the route, flight safety is perceived as the highest rate of observation of all operational-control functions of the aircraft. The given functions of the aircraft are observable and identifiable by the systems and cognitive perceptions of the pilot. Situational control of the aircraft on the route with the identification of the danger, into which the pilot can get is perceived as an exact element of failure. If the pilot enters such a situation, apriori solutions are offered to him/her by the aircraft information system. The character and emergency solution in the highest criticism of the failure of aircraft systems is the controlled landing in the local safety corridor when guiding the aircraft on the selected route. The aim of the article is the theory of the solution for the introduction of an assistance element in small aircraft with a description of the solution of autonomous choice of geolocation in a defined local environment. By a heuristic experiment in the article, let’s prove the methods of selection of geographical areas for landing an aircraft with the possibility of introduction into the aircraft information system. The article presents the methodology of creation autonomous assistance system, based on the measurement of detection areas for landing with the collection of data from the GIS system. This system can assist in pilot training and real flights for small aircraft without difficulty. The effectiveness of such system and the parameterization of its data were shown and proved. The developed models may be further used for creation an autonomous selection system in the event of accidental aircraft failures